SUKSESI BAKTERI PADA FERMENTASI KULIT BUAH NANAS (Ananas comosus (L.) Merr) - Pelealu, Irna W.; Lawalata, Helen J.; Tengker, Anita C.; Posumah, Danny (SOSCIED, 2024)
The utilization of pineapple peel in the fermentation process produces bacteria and probiotics that are beneficial for human health. The fermentation process is carried out to enhance the nutrition, shelf life, and organoleptic properties of food products. The presence of microbes, especially bacteria, is believed to play an important role in the fermentation process of pineapple peel. However, the specific bacteria involved in the fermentation of pineapple peel are not yet fully known. The aim of this research is to study the bacterial succession during the fermentation of pineapple peel (Ananas comosus (L.) Merr) and to identify the types of bacteria obtained during the fermentation process. This research uses a qualitative descriptive laboratory-based method by conducting morphological identification of bacteria and biochemical testing to determine the types of bacteria present in the fermentation of pineapple peel. Based on the identification data, 11 bacterial isolates were found during the fermentation of pineapple peel. The isolates were identified macroscopically and then subjected to a series of biochemical tests. The results of the research indicate that the microorganisms involved in the fermentation of pineapple peel belong to the genera Staphylococcus sp., Bacillus sp., and Lactobacillus sp.. The microbial succession during pineapple peel fermentation shows that the bacterial population of the genus Staphylococcus sp. dominates on day 0 of fermentation, while the genus Bacillus sp. undergoes a succession pattern, experiencing growth on day 1 and continuing to increase until day 3. Meanwhile, bacteria from the genus Lactobacillus sp. only appeared on day 1 of fermentation.